Writing effective lesson plans : the 5-star approach - Serdyukov, Peter. 4 0 16; 1947- Ryan, Mark; 5 (Boston : Pearson/Allyn and Bacon, 2008)
Provides guidance and tools for writing effective lesson plans, covering structure, lesson description, goals, objectives, materials, tools, procedure, assessment, evaluation, time efficiency, knowledge construction, skill development, and strategic and tactical planning.
Structure and stages of development -- Lesson description -- Goals and objectives -- Materials and tools -- Procedure -- Reflective assessment and evaluation -- Time efficiency in teaching and learning -- Knowledge construction and skill development -- Course and lesson : strategic and tactical planning -- Implementing the plan -- Extending the lesson plan to home -- Teacher professional competence.
Includes bibliographical references (p. 239-241) and index.
Professional;Professional
Keywords: 2 -- 0; 6; Lesson planning.;Lesson planning; 20; 2